Progress in the Chemistry of Organic Natural Products 107 (Progress in the Chemistry of Organic Natural Products,, 2018)
The first review describes examples of very promising compounds discovered from plants acquired from Africa, Southeast Asia, the Americas, and the Caribbean region with potential anticancer activity. These include plant secondary metabolites of the diphyllin lignan, penta[b]benzofuran, triterpenoid, and tropane alkaloid types. The second review presents 40 more erythrinan alkaloids, which were either new or were missed out in the last major reviews, bringing to a total of 154 known erythrinan alkaloids known to date. The reported pharmacological activities of the new and known alkaloids showed a greater bias towards central nervous system and related activities. Other prominent activities reported were antifeedant or insecticidal, cytotoxicity/antitumor/anticancer/estrogenic, antiprotozoal, antiinflammatory, antioxidant, antifungal and antiviral activities.